The Psychology of Coercion Failure: How Reactance Explains Resistance to Threats. Issue 1 (22nd June 2022) - Powers, Kathleen E.; Altman, Dan
Abstract: When confronted with coercive threats, targets often stand firm rather than back down. We identify one important yet unrecognized factor that causes actors to resist threats: psychological reactance. Reactance theory explains that when someone perceives a threat to their freedom to make choices, they attempt to restore their autonomy by refusing to capitulate. The result is unwillingness to concede to coercion that extends beyond rational incentives. We test for reactance as a cause of coercion failure with two novel experiments. Each experiment pairs a coercive threat treatment with a matched "natural costs" counterpart that imposes the same choice on the target without intentional action by a coercer. Controlling for prominent alternative explanations, including costs, benefits, power, credibility, and reputation, we find that the targets of threats capitulate less frequently and more often support aggression against their opponents.